After the Splits: Information Flow between Bitcoin and Bitcoin Family. (January 2021) - Yi, Eojin; Cho, Yerim; Sohn, Sungbin; Ahn, Kwangwon
Highlights: An asymmetric information flow exists from the original coin to its split. The Bitcoin market, with a larger transaction volume and less uncertainty, has price leadership over Bitcoin Cash. The characteristics exhibited by the original coin could begin to emerge in the maturing split markets. Abstract: This study examines information flow between new and old forks after Bitcoin splits. Particularly, we estimate the transfer entropy between Bitcoin and Bitcoin Cash as an information-theoretic approach. When a symbolic analysis is applied, asymmetric information flow from Bitcoin to Bitcoin Cash is observed. We further provide evidence that this relationship is due to the role of liquidity in price leadership. Our findings suggest that (i) investors could forecast the fluctuation of price evolution in the Bitcoin Cash using the rise–fall pattern of Bitcoin price and (ii) policymakers (regulators) must closely monitor the information flow between the two markets, in a state with strong market integration, to prevent market distortion and regulatory arbitrage.